Experimental and theoretical study on the formation of volatile sulfur compounds under gas reservoir conditions. (February 2021) - Meshoulam, Alexander; Said-Ahmad, Ward; Turich, Courtney; Luu, Nathalie; Jacksier, Tracey; Shurki, Avital; Amrani, Alon
Highlights: Short alkyl thiols and thiophenes are the main products of the pyrolysis of pentane and H2 S at 360 °C. Thiols and thiophens have distinct δ 34 S values at different stages of thermal maturation. Thiophenes and aromatic fused thiophenes can preserve their original δ 34 S longer than thiols. Thiophenes are not likely products form reactions of H2 S and hydrocarbons under gas reservoir conditions. The δ 34 S of thiols and thiophenes can be used to study their origin and alterations in natural gas reservoirs. Abstract: Volatile organic sulfur compounds (VOSC) are found in petroleum natural gas and condensates at trace levels. The abundance and δ 34 S values of VOSC were proposed as a proxy for thermal processes such as oil and gas generation during thermal maturation, thermochemical and microbial sulfate reduction, migration and expulsion. The understanding of VOSC formation and degradation mechanisms is needed to refine the use of δ 34 S values of VOSC as proxies for thermal processes over geological timescales in the subsurface. We therefore conducted pyrolysis experiments at 360 °C for 4, 12 and 72 h using pentane and H2 S or pentanethiol as model compounds to study the formation and degradation pathways of VOSC and associated variations in δ 34 S values. The main products of these experiments are C1 -C4 alkanes along with a variety of thiols and thiophenes, the most dominant VOSC formed. Most thiols were in equilibrium with H2 S after 4 h based on their δ 34 S values. Thiophenes were first 34 S depleted relative to H2 S and only reached equilibrium at the 72 h experiment. The products and 34 S fractionations in the pyrolysis experiment of pentanethiol at 360 °C and 12 h were similar to those of the experiment with H2 S and pentane at the same conditions. This similarity suggests that pentanethiol is an intermediate product in the formation of aromatic VOSC during pyrolysis of pentane and H2 S. Benzo- and dibenzothiophenes (BTs and DBTs) were formed in the liquid phase and their 34 S depleted values relative to H2 S indicated that they had not reached equilibrium. Ab-initio calculations of the thermodynamic properties of thiols, thiolanes, thiophenes BTs and DBTs were used to explain the relative abundance of products in the system and predict their abundance and S isotopic signature at reservoir conditions. The thermodynamic data suggests that at equilibrium, only small quantities of thiols and even smaller quantities of thiolanes can exist under our experimental conditions. Unlike thiols, the free energy of formation of thiophenes, BTs and DBTs is negative under these conditions indicating that the formation of these compounds is thermodynamically favored. The result suggests that the δ 34 S values of thiols are controlled by a very rapid equilibrium isotopic effect (EIE). On the other hand, aromatic sulfur compounds can preserve the δ 34 S value of the kinetic isotopic effect (KIE) associated with their formation for longer. However, under typical petroleum reservoir conditions, the formation of aromatic VOSC in the gas phase from short alkanes (5 ) and H2 S is not thermodynamically preferred and thus their presence is expected to be either as kinetic products or due to influx and charge from a different source where the reactions were thermodynamically favorable. Thus, the abundance and Δ 34 S between H2 S and VOSC can be used as a new approach to evaluate charge history within sulfur containing reservoirs.